2000
DOI: 10.1002/1097-0223(200008)20:8<652::aid-pd882>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Second-trimester prenatal screening for Down syndrome and the relationship of maternal serum biochemical markers to pregnancy complications with adverse outcome

Abstract: In a group of 26 524 control pregnancies and a group of 3728 pregnancies affected by one or more of the pregnancy complications of low birthweight, intra‐uterine growth restriction (IUGR), preterm delivery and stillbirth, I have compared the relative risk of occurrence of these complications in pregnancies which had a raised maternal serum AFP (>2.0 MoM), raised maternal serum free β‐hCG (>2.0 MoM), low AFP (<0.5 MoM), low free β‐hCG (<0.5 MoM), combined raised AFP and free β‐hCG (>2.0 MoM), and in those with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…Infants of mothers with hyperemesis have lower birth weights and the mothers are more likely to have infants that are small for gestational age (8). Although elevated maternal serum AFP level usually shows an elevated risk for neural tube defects, they are also related to adverse pregnancy outcomes such as preeclampsia, spontaneous abortion, preterm delivery, low birth weight, IUGR, oligohydramnios, placental abruption and stillbirth (9)(10)(11)(12), all of which are thought to be associated with abnormal placentation (13). In our study, a significant association between serum AFP values and IUGR was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants of mothers with hyperemesis have lower birth weights and the mothers are more likely to have infants that are small for gestational age (8). Although elevated maternal serum AFP level usually shows an elevated risk for neural tube defects, they are also related to adverse pregnancy outcomes such as preeclampsia, spontaneous abortion, preterm delivery, low birth weight, IUGR, oligohydramnios, placental abruption and stillbirth (9)(10)(11)(12), all of which are thought to be associated with abnormal placentation (13). In our study, a significant association between serum AFP values and IUGR was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ashour et al (23) suggested that the utility of hCG level as a screening test for preeclampsia was limited. Besides, the relationship between obstetric complications and elevated hCG levels was not confirmed in two other studies (10,24). In another study, preterm delivery, preeclampsia and large for gestational age were found to be associated with only hCG levels of 3 MoM and the authors concluded that increased fetal surveillance is not warranted with lower values (25).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kirkegaard et al demonstrated a strong association between free β-hCG levels below 0.3 MoM and SGA fetuses [77]. Finally, in a group of 3728 pregnancies affected by one or more of the pregnancy complications of low birth weight, IUGR, PTD and stillbirth, first-trimester free β-hCG levels below 0.5 MoM showed relative risks of 2.3 for developing IUGR [78]. It is still necessary to specify that there are conflicting opinions on the role of free β-hCG in PE and IUGR [11].…”
Section: Prognostic Toolsmentioning
confidence: 99%
“…Appendix 5, Table 79 summarises each study's salient features. [153][154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171] One citation contributed to two separate studies and results. 156 The most common gestation tested was the mid-trimester (14-28 weeks commonly reported their results were 2.0 and 2.5 multiples of the median (MoMs).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…There were 23 primary articles, of which 19 evaluated the use of mid-trimester maternal serum hCG as a predictor of spontaneous preterm birth (n = 177,730 women) 157,158,162,165,166,[184][185][186][187][188][189][190][191][192][193][194][195][196][197] while one article evaluated it in early first trimester (n = 169), 198 and three articles evaluated cervicovaginal hCG as a predictor of spontaneous preterm birth in women who presented with symptoms of threatened preterm labour (n = 248). 139,199,200 Appendix 5, Table 85 summarises each study's salient features, stratified according to the population of women tested, i.e.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%